Crenotherapy as a Complementary and Integrative Treatment for Chronic Rhinosinusitis: A Systematic Review and Discussion of Current Evidence Limitations. Issue 4 (July 2022) - Nimmagadda, Sai V.; Schmale, Isaac L.; Man, Li-Xing
Background: Chronic rhinosinusitis (CRS) is a common condition that affects patients' quality of life. Standard treatments for CRS have known side effects and variable efficacy rates. Thus, complementary and integrative (CIM) treatments for CRS such as crenotherapy, which utilizes high mineral content water or vapor as an inhalation therapy, are of continued interest. Objectives: To summarize and evaluate the current research investigating crenotherapy's therapeutic potential and clinical outcomes for the treatment of CRS. Study Design: Systematic review and qualitative analysis. Methods: A systematic review was performed, with a comprehensive search strategy applied to 6 databases from inception to March 2021: CINAHL, Cochrane, Embase, PubMed, Scopus, and Web of Science. Studies with at least 10 patients, which investigated crenotherapy as the sole or adjunctive treatment for CRS in humans were included. Results: In total, 10 articles out of 756 were included. Of these, 6 were randomized controlled trials. The remaining four articles were non-randomized prospective cohort studies. Six studies assessed clinical symptoms in response to crenotherapy, and there were unanimous improvements in Visual Analog Scale (VAS), Sino-Nasal Outcome Test-20 (SNOT-20), and other quality of life metrics. The studies that assessed inflammatory markers, cytology, or other measures showed significant improvement in neutrophil count, spores, ciliary motility, IgE, and manometry. Minimal to no adverse events were reported across all 10 studies. Conclusion: There is limited data to support crenotherapy's effectiveness in treating patients with CRS. However, published studies suggest that for certain patients crenotherapy can both improve CRS symptoms and objective measures of nasociliary function with minimal side effects. Findings must be interpreted with caution due to study heterogeneity, inconsistent use of standard CRS definitions and outcomes measures, as well as other study design flaws. Given these results, as well as a growing interest in CIM, crenotherapy treatments for CRS deserve further investigation.